The impact of social, economic and cultural Islamic Persian Market On Andishe new town sustainability - مجید کفاشی (توسعه اجتماعی, 2016)
This paper is the result of research projects.This study aimed to identify the impact of social, economic and cultural sustainability of Islamic Persian Market using Bourdieu's perspective and a Leonard Duhl.Survey asking what the relationship between the impact of social, economic and cultural market Persian - Islam (during the construction and completion of construction) and the stability of the new town idea there?Strengths and weaknesses of major market projects in Iran - Islamic Thought and sustainability are the new city?Methodology of the survey instrument, a questionnaire based on a Likert scale of five options.Content validity assessment, 83/0, and construct validity using factor analysis and statistical techniques to 90/0 at the top and shows the correlation between the scale items.The subjects in this study were 524 local residents and shopkeepers of ideas are.Sampling method is based on systematic manner.To test the hypotheses and to test the regression model, the fit indices of LISREL software is usedOur findings indicate that during construction, the economic impact of variable rate 14/0 and variable social impact with 18/0 and varying cultural impact of 21/0, the dependent variable to be predicted resilience of Thought. At the end of construction, the economic impact of variable rate 19/0 and variable social impact with a rate of 15/0 and cultural impact of variable rate 0/31, the dependent variable can be predicted resilience of Thought.